Population biological traits of Periophthalmus chrysospilos Bleeker, 1853 in the Vietnamese Mekong Delta - Dinh,Quang Minh; Nguyen,Ton Huu Duc; Nguyen,Tien Thi Kieu; Lam,Tran Thi Huyen; Truong,Ngon Trong; Tran,Dinh Dac (PeerJ, 2022)
Periophthalmus chrysospilos is an amphibious fish living in mudflats from eastern India to Indonesia, including the Vietnamese Mekong Delta. Population biological traits play an important role in fishery assessment, but understanding is limited for this species. In total 1,031 specimens were caught in two regions covering four provinces, including the TVST (Duyen Hai, Tra Vinh and Tran De, Soc Trang) and BLCM (Dong Hai, Bac Lieu and Dam Doi, Ca Mau). Results found that the sex ratio was close to 1:1. The parameters of the von Bertalanffy in TVST were L∞ = 12.8 cm, K = 0.41 yr−1, t0 = −0.10 yr and in BLCM were 12.7 cm, 0.38 yr−1 and −0.08 yr, respectively. Although the growth coefficient (Φ′) in BLCM (1.79), was lower than that in TVST (1.83), the species shared a similar size at first capture (7.9 cm in TVST and 7.9 cm in BLCM). The species suffered from heavy pressure of fishing in TVST as fishing mortality in TVST (2.32 yr−1) was higher than that in BLCM (1.38 yr−1), leading to the higher total mortality (Z = 3.60 yr−1) in TVST compared to BLCM (Z = 2.59 yr−1). By contrast, the species showed similar natural mortality over both sites (1.20 yr−1 in TVST and 1.22 yr−1 in BLCM). The Periophthalmus chrysospilos population was reasonably exploited because E values (0.64 in TVST and 0.53 in BLCM) were lower than E10 (0.706 in BTTV and 0.705 in STBL). Nonetheless, to avoid the consequences of overfishing, some sustainable fisheries practices should be implemented, such as protecting mangrove forests, restricting fishing during the recruitment period, using appropriate fishing tools and increasing mesh size.
Keywords: Exploitation rate; Fishing mortality; Growth coefficient; Mudskipper; Natural mortality; Size at first capture; Total mortality